Syrian Refugee Children's Education in Turkish Public Schools: Primary School Teachers' Experiences - Nurhan ATALAY; Zeynep KILIC; Burcu ANILAN; Huseyin ANILAN; Sengul S. ANAGUN (Anı Publishing, 2022)
This study aims to explain the problems encountered in the education of Syrian children with the experiences of Turkish teachers. A descriptive qualitative research method was used for the study. The participants of the study were 70 elementary school teachers. The participants were selected based on the sampling criterion. The study data were collected through structured interviews. The participants were asked structured questions, and they responded as written to the questions. At the end of the study, the most significant responsibility in Syrian 'children's adjustment to the education system in Turkey falls on the shoulders of primary school teachers. Turkish primary school teachers clearly stated that the main reason for all problems they experienced was the language difference. The study results revealed that not being able to solve the communication problem deepens the problem and creates an emotional pressure on primary school teachers refugee children.